POSTER TIGA RONDE: AN APPRAISAL ANALYSIS OF NEGATIVE COMMENTS ON TWITTER - Zulfa, Nadiyah; Herliani, Indah Kurnia (Sanata Dharma University, Yogyakarta, 2023)
This paper discusses the negative comments on the tweets attacking the